Penemuan Mikrofilaria Brugia malayi di Wilayah yang Telah Lulus Transmission Assesment Survey (TAS-3) di Kabupaten Kotawaringin Barat Provinsi Kalimantan Tengah - nita rahayu; Yuniarti Suryatinah; Paisal Paisal (ASPIRATOR - Journal of Vector-borne Disease Studies, 2019)
Abstract Kotawaringin Barat is a filariasis endemic area and has been undergoing mass drugs adminstration (MDA) for 5 years. The district passed third phase of Transmission Assesment Survey (TAS-3) in 2016. In the TAS-3, we found 4 children with filariasis antibodies. In this study, we performed microscopic examination of microfilaria to confirm the results of TAS-3, as well as the measurement of knowledge, attitudes, and behavior towards the treatment of filariasis. The study was conducted in Dawak Village and Sungai Bakau Village, with a total sample of 620 respondents. The results of microscopic examination are 5 respondents with Brugia malayi in their blood, consisting of 4 respondents in Dawak Village and 1 respondent in Sungai Bakau Village. The percentage of respondents who know the causes and symptoms of filariasis is very small. Although most respondents have a positive attitude towards treatment, the right treatment behavior is still very low. One respondent was found to be reinfected with B. malayi. In addition, it is suspected that there is transmission from animals to humans, but it still needs further investigation.